The Mechanisms Leading to Distinct Responses to PD-1/PD-L1 Blockades in Colorectal Cancers With Different MSI Statuses - Cui, Guanglin (Frontiers in Oncology, 2021)
Current clinical studies showed distinct therapeutic outcomes: in which CRC patients with mismatch repair-deficient (dMMR)/microsatellite instability high (MSI-H) seem to be relatively more “sensitive” in response to anti-programmed death-1 receptor (PD-1)/programmed death-1 receptor ligand 1 (PD-L1) therapy than those with mismatch repair-proficient (pMMR)/microsatellite instability-low (MSI-L). The mechanisms by which the same PD-1/PD-L1 blockades lead to two distinct therapeutic responses in CRC patients with different MSI statuses remain poorly understood and become a topic of great interest in both basic research and clinical practice. In this review of the potential mechanisms for the distinct response to PD-1/PD-L1 blockades between dMMR/MSI-H CRCs and pMMR/MSI-L CRCs, relevant references were electronically searched and collected from databases PubMed, MEDLINE and Google scholar. Sixty-eight articles with full text and 10 articles by reference-cross search were included for final analysis after eligibility selection according to the guidelines of PRISMA. Analysis revealed that multiple factors e.g. tumour mutation burden, immune cell densities and types in the tumour microenvironment, expression levels of PD-1/PD-L1 and cytokines are potential determinants of such distinct response to PD-1/PD-L1 blockades in CRC patients with different MSI statuses. Which might help clinicians to select candidates for anti-PD-1/PD-L1 therapy and improve therapeutic response in patients with CRC.